Аналітичні інструменти в управлінні публічними фінансами: сучасні практики та виклики - Качула, Світлана Валентинівна; Kachula, Svitlana (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
Застосування аналітичних засобів стало одним із головних чинників удосконалення системи управління державними фінансами, сприяючи більш раціональному використанню бюджетних ресурсів, зміцненню відкритості фінансових операцій та посиленню контролю з боку органів влади на всіх рівнях. У статті проведено аналіз теоретико-методологічних основ аналітики, а також розглянуто сучасні практики її застосування у державах-лідерах світової економіки, країнах Східної Європи та в Україні. Акцентовано увагу на виявленні основних викликів і обмежень, таких як фрагментарність систем, недостатня якість і сумісність даних, кадровий дефіцит та обмежений політичний запит на аналітичну підтримку прийняття рішень. Наголошено на необхідності розробки і впровадження національної стратегії розвитку аналітики, модернізації цифрової інфраструктури та посилення компетентності фахівців. Запропоновано практичні рекомендації для удосконалення бюджетного аналізу і впровадження data-driven підходів в управлінні публічними фінансами, що сприятимуть зміцненню підзвітності та сталому розвитку. Analytical tools play a crucial role in the modernization of public finance management by enhancing the efficiency, transparency, and accountability of the budgeting process at various levels of government. This article presents a comprehensive analysis of the theoretical and methodological foundations of analytics, alongside a detailed examination of contemporary practices of their application in leading countries worldwide, as well as in Eastern European nations and Ukraine. Particular attention is given to identifying key challenges and limitations, such as fragmented systems, insufficient data quality and interoperability, shortage of qualified personnel, and limited political demand for analytical support in decision-making. The study emphasizes the necessity of developing and implementing a national strategy for analytics advancement, modernizing digital infrastructure, and strengthening the competencies of specialists in the public finance sector. Practical recommendations are proposed to improve budget analysis processes and promote data-driven approaches in public finance management. These measures are expected to contribute significantly to enhancing fiscal accountability and supporting sustainable development. The findings underscore the importance of integrating analytical tools as a fundamental element of strategic governance, enabling timely identification of fiscal risks, evidence-based policymaking, and efficient resource allocation. Furthermore, the article highlights successful examples of analytical tool implementation in Eastern European countries, illustrating potential pathways for Ukraine’s digital transformation in public finance. The research contributes to the growing discourse on digital governance and offers actionable insights for policymakers, financial managers, and researchers aiming to foster innovation and transparency in public sector financial management.
Analytical tools in public finance management: current practices and challenges
Keywords: аналітичні інструменти; analytical tools; публічні фінанси; public finance; управління бюджетом; budget management; фінансова аналітика; financial analytics; бізнес-аналітика; business intelligence; цифрові технології; digital technologies; прогнозування; forecasting; сценарний аналіз; scenario analysis; прозорість фінансів; financial transparency